2007
DOI: 10.1083/jcb.200610042
|View full text |Cite
|
Sign up to set email alerts
|

Bax/Bak promote sumoylation of DRP1 and its stable association with mitochondria during apoptotic cell death

Abstract: Dynamin-related protein 1 (DRP1) plays an important role in mitochondrial fission at steady state and during apoptosis. Using fluorescence recovery after photobleaching, we demonstrate that in healthy cells, yellow fluorescent protein (YFP)–DRP1 recycles between the cytoplasm and mitochondria with a half-time of 50 s. Strikingly, during apoptotic cell death, YFP-DRP1 undergoes a transition from rapid recycling to stable membrane association. The rapid cycling phase that characterizes the early stages of apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
424
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 483 publications
(441 citation statements)
references
References 70 publications
(144 reference statements)
12
424
1
4
Order By: Relevance
“…Studies showed that Bax and Drp1 are binding partners, and Drp1 promotes mitochondrial translocation of Bax 51. Though both Bax and Drp1 translocate to discrete foci on the mitochondria, studies showed that mitochondrial Bax participates in apoptotic fragmentation of mitochondria by stabilizing Drp1 52, 53, 54. Mitochondrial Drp1 promotes Bax oligomerization and leads to cytochrome C release from mitochondria 55.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that Bax and Drp1 are binding partners, and Drp1 promotes mitochondrial translocation of Bax 51. Though both Bax and Drp1 translocate to discrete foci on the mitochondria, studies showed that mitochondrial Bax participates in apoptotic fragmentation of mitochondria by stabilizing Drp1 52, 53, 54. Mitochondrial Drp1 promotes Bax oligomerization and leads to cytochrome C release from mitochondria 55.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is confirmed by results showing that Bid induces the oligomerization and insertion of Bax in the MOM, 33 and Bax was also found to co-localize with Drp1 at fission sites. 28,37 Further, very recent findings demonstrated Drp1 recruitment to cardiolipin-rich membrane sites as a prerequisite for the formation of membrane hemifusion/fission structures and Bax oligomerization. 11,28 Notably, Drp1-induced Bax oligomerization at mitochondrial fission sites also required the presence of tBid, which further supports the conclusion that both, Drp1 and Bid concomitantly contribute to mitochondrial death pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has indicated that Drp1 accumulates on mitochondria during apoptosis due to Bax/Bak-dependent sumolylation of Drp1, which results in stable membrane association of Drp1 with mitochondria and thus increased fission (Wasiak et al, 2007;Zunino et al, 2007). There is also evidence to suggest that mitochondrial fusion is blocked upon activation of apoptosis indicating that the fragmented phenotype may occur due to a combination of increased fission and decreased fusion (Karbowski et al, 2004).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%